Emergency General Anesthesia with Rapid Sequence Intubation for Cesarean Delivery in Severe Eclampsia Complicated by Pulmonary Edema and Premature Rupture of Membranes: A Multidisciplinary Critical Care Case Report - Muhammad Ibrahim; Propan Hanggada Satyamakti Mubarak (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Eclampsia complicated by acute pulmonary edema is a life-threatening obstetric emergency that demands rapid, coordinated multidisciplinary intervention. Premature rupture of membranes (PROM) coexisting with refractory eclamptic seizures and respiratory failure further heightens maternal-fetal risk and complicates anesthetic decision-making. Optimal management requires individualized airway strategy, aggressive seizure control, and meticulous fluid balance under intensive care. Case presentation: A 28-year-old primigravida at term was referred from the emergency department after two generalized tonic-clonic seizures (5 minutes each), with severe hypertension (168/95 mmHg), tachypnea (RR 30/min), Glasgow Coma Scale 12 (sopor), bilateral basal rales, and oxygen desaturation to 92% on room air. Laboratory studies showed proteinuria +2, elevated transaminases (SGOT 62 U/L), and a PaO₂/FiO₂ ratio of 423 mmHg consistent with non-cardiogenic pulmonary edema. Emergency cesarean delivery was performed under general anesthesia with rapid sequence intubation (lidocaine-dexamethasone pretreatment, ketamine-propofol induction, rocuronium paralysis). A live male neonate (3420 g, APGAR 7-8-9) was delivered; surgery duration was 45 minutes. In the ICU, lung-protective mechanical ventilation, continuous furosemide infusion (5 mg/h, negative fluid balance strategy), and escalating multimodal anticonvulsant therapy (magnesium sulfate, midazolam, phenytoin) for refractory seizures were employed. The patient was extubated after 16 seizure-free hours, transferred to the ward on day 3, and discharged with her infant on day 4. Conclusion: Early recognition of eclampsia with pulmonary edema, individualized rapid sequence intubation general anesthesia, multimodal seizure control, and aggressive negative fluid balance under multidisciplinary critical care can yield favorable maternal-neonatal outcomes even in resource-constrained settings.